A NEW VIEW IN THE ACCOUNTING PROFESSION - Pirakhunova F. N.; Astanakulov N. T. (American Journals, 2024)
In recent years, the economy of Uzbekistan has seen significant growth in macroeconomic indicators, and the financial performance of domestic companies has also improved. In this regard, experienced and professional accountants are needed. The authors believe that in economics, the global accounting profession would be recognized as a leader in developing strong and sustainable organizations, financial markets and national economies and future adaptation to the requirements of International Financial Reporting Standards (IFRS).
Keywords: Accountant, specialty, accounting, cognitive technology, Luca Pacioli.